2019
DOI: 10.1128/mbio.01743-19
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella Adenylate Cyclase Toxin Inhibits Monocyte-to-Macrophage Transition and Dedifferentiates Human Alveolar Macrophages into Monocyte-like Cells

Abstract: Monocytes arriving at the site of infection differentiate into functional effector macrophages to replenish the resident sentinel cells.Bordetella pertussis, the pertussis agent, secretes an adenylate cyclase toxin-hemolysin (CyaA) that binds myeloid phagocytes through complement receptor 3 (CD11b/CD18) and swiftly delivers its adenylyl cyclase enzyme domain into phagocytes. This ablates the bactericidal capacities of phagocytes through massive and unregulated conversion of cytosolic ATP into the key signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In contrast, the more phagocytic and highly bactericidal mature macrophages are capable of self-renewal ( 6 ). We observed that exposure of monocytes to CyaA/cAMP signaling blocked M-CSF-driven formation of intracellular granules and prevented development of larger Golgi bodies and the formation of an expanded ER network typical for the mature macrophage cells ( 6 , 42 44 ). Hence, CyaA/cAMP-elicited signaling restricted development of organelles required for enhanced synthesis and secretion of cytokines and providing membranes for formation of phagosomes ( 45 47 ).…”
Section: Bordetella Pertussis Adenylate Cyclase Toxin Subvermentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast, the more phagocytic and highly bactericidal mature macrophages are capable of self-renewal ( 6 ). We observed that exposure of monocytes to CyaA/cAMP signaling blocked M-CSF-driven formation of intracellular granules and prevented development of larger Golgi bodies and the formation of an expanded ER network typical for the mature macrophage cells ( 6 , 42 44 ). Hence, CyaA/cAMP-elicited signaling restricted development of organelles required for enhanced synthesis and secretion of cytokines and providing membranes for formation of phagosomes ( 45 47 ).…”
Section: Bordetella Pertussis Adenylate Cyclase Toxin Subvermentioning
confidence: 80%
“…and prevented development of larger Golgi bodies and the formation of an expanded ER network typical for the mature macrophage cells (6,(42)(43)(44). Hence, CyaA/cAMP-elicited signaling restricted development of organelles required for enhanced synthesis and secretion of cytokines and providing membranes for formation of phagosomes (45)(46)(47).…”
Section: Bordetella Pertussis Adenylate Cyclase Toxin Subverts Monocymentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we use 50 ng/ml of PTX to treat the culture microglia, which did not change the cells into small and rounded macrophages; the microglia showed a similar morphology as control, suggesting that PTX, at least at this concentration of 50 ng/ml, is not toxic to microglia, and it can inhibit the LPS effect to microglia. In another article (Ahmad et al, 2019), at 2.75 ng/ml, PTX can inhibit maturation of human monocyte precursors into the more phagocytic macrophage cells. It is similar to our data.…”
Section: Discussionmentioning
confidence: 95%